ANALISIS KUALITAS LIMBAH CAIR PADA INSTALASI PENGOLAHAN LIMBAH CAIR (IPLC) RUMAH SAKIT UMUM LIUN KENDAGE TAHUNA TAHUN 2010 - Ferdy G. Pakasi (Jurnal Kesehatan Lingkungan, 2011)
Hospital waste water is one source of potential environmental pollutant because it is necessary the management of waste water before it is disposed in to public channels. This study is a descriptive analytic study, in which the writer wanted to describe how the quality of liquid waste in the RSU Liun Kendage Tahuna, in particular the parameters BOD, COD, TSS and pH through laboratory tests. The results of this study indicate that the average BOD eligible (28.6 mg /l) is smaller than the raw waste water quality for hospital activities that have been assigned to 30 mg / l, the average COD is not eligible (83.8 mg /l) exceeding effluent quality standard of 80 mg / l, mean TSS is not eligible (31.3 mg /l) exceeds the effluent quality standard of 30 mg /l and pH of the eligible 6.6 to 7.8 with a value the average pH = 7.1. The qualit of waste water effluent discharged IPLC on the urban public channel after processing qualify with levels of BOD value = 7 mg / l, COD = 25 mg / l, TSS = 11 mg / l and pH = 6.8. To further improve the quality of effluent RSU Liun Kendage Tahuna, the need for repair of damaged pipelines, periodic monitoring and better management of IPLC.